2019
DOI: 10.1038/s41467-019-09540-z
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory cortical forces promote three dimensional cell intercalations that shape the murine mandibular arch

Abstract: Multiple vertebrate embryonic structures such as organ primordia are composed of confluent cells. Although mechanisms that shape tissue sheets are increasingly understood, those which shape a volume of cells remain obscure. Here we show that 3D mesenchymal cell intercalations are essential to shape the mandibular arch of the mouse embryo. Using a genetically encoded vinculin tension sensor that we knock-in to the mouse genome, we show that cortical force oscillations promote these intercalations. Genetic loss-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 84 publications
(92 reference statements)
4
88
0
Order By: Relevance
“…In our study, decreased YAP nuclear localization was observed in Piezo1-deficient mice, resulting in impaired collagen II and IX expression which leads to increased bone resorption. YAP/TAZ and PIEZO1 serve as downstream effectors of Wnt5a-mediated actomyosin polarity and cytosolic calcium transients that orient and drive three-dimensional cell intercalations that shape the murine mandibular arch 42 . It remains to be investigated whether Wnt5a will regulate the PIEZO1-YAP-collagen pathway in mechanotransduction mediated bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, decreased YAP nuclear localization was observed in Piezo1-deficient mice, resulting in impaired collagen II and IX expression which leads to increased bone resorption. YAP/TAZ and PIEZO1 serve as downstream effectors of Wnt5a-mediated actomyosin polarity and cytosolic calcium transients that orient and drive three-dimensional cell intercalations that shape the murine mandibular arch 42 . It remains to be investigated whether Wnt5a will regulate the PIEZO1-YAP-collagen pathway in mechanotransduction mediated bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…The precision of these implications has been improving as we move from hypothetical assertions [ 3 ] to relative measurements [ 4 ], to absolute measurements [ 5 7 ] coupled with theory [ 7 9 ]. With regard to forces, the magnitude and directional bias, or polarity, of cytoskeletal contractions are relevant to how cells rearrange and bias the shapes of tissue sheets and bulk mesenchymal structures [ 5 , 10 14 ]. The magnitudes and spatial distributions of tissue properties also influence the growth and form of tissues by mechanisms that are being elucidated [ 9 , 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to forces, the magnitude and directional bias, or polarity, of cytoskeletal contractions are relevant to how cells rearrange and bias the shapes of tissue sheets and bulk mesenchymal structures [ 5 , 10 14 ]. The magnitudes and spatial distributions of tissue properties also influence the growth and form of tissues by mechanisms that are being elucidated [ 9 , 11 , 14 ]. Outstanding questions are whether and how tissue properties regulate anisotropic processes such as convergent extension.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a growing body of evidence indicates that Wnt proteins can activate YAP1/TAZ, independent of Wnt/β-catenin signaling in many cell lines [47][48][49][50][51]. An alternative Wnt pathway has been promulgated, consisting of Wnt, FZD/ROR, Ga12/13, Rho GTPases, LATS1/2, and YAP1/TAZ, wherein YAP1 and TAZ are the key downstream transcription cofactors [49].…”
Section: Interaction Of Hippo-yap1/taz Signaling With the Wnt Pathwaymentioning
confidence: 99%
“…Wnt3a activates the Wnt-YAP1/TAZ pathway to maintain the pluripotency of bovine trophoblast stem cells (TSCs) [50]. The Wnt5a-induced YAP1/TAZ activation mediates cell polarity and formation of organ primordia [47]. Wnt-activated YAP1 regulates rostral and caudal brain tissue identity and affects neural tissue from human-induced pluripotent stem cells (hiPSCs) [51].…”
Section: Interaction Of Hippo-yap1/taz Signaling With the Wnt Pathwaymentioning
confidence: 99%